2015
DOI: 10.3168/jds.2014-8971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved oxygen on redox potential and milk acidification by lactic acid bacteria isolated from a DL-starter culture

Abstract: Milk acidification by DL-starter cultures [cultures containing Lactococcus lactis diacetylactis (D) and Leuconostoc (L) species] depends on the oxidation-reduction (redox) potential in milk; however, the mechanisms behind this effect are not completely clear. The objective of this study was to investigate the effect of dissolved oxygen on acidification kinetics and redox potential during milk fermentation by lactic acid bacteria (LAB). Fermentations were conducted by single strains isolated from mixed DL-start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…lactis DSM20481 T was grown exponentially during the first 8 h fermentation and reached the stationary phase after 10 h fermentation at a cell density of 8.5 Log 10 cfu/mL. Growth kinetics of L. lactis DSM20481 T in milk was not significantly affected by treatments (data not shown), in accordance with reported effects of initial oxygen on L. lactis fermentations (Cretenet et al, 2014;Larsen et al, 2015).…”
Section: Fermentation Kinetic and Sampling For Microarray Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…lactis DSM20481 T was grown exponentially during the first 8 h fermentation and reached the stationary phase after 10 h fermentation at a cell density of 8.5 Log 10 cfu/mL. Growth kinetics of L. lactis DSM20481 T in milk was not significantly affected by treatments (data not shown), in accordance with reported effects of initial oxygen on L. lactis fermentations (Cretenet et al, 2014;Larsen et al, 2015).…”
Section: Fermentation Kinetic and Sampling For Microarray Analysissupporting
confidence: 89%
“…We showed recently that initial levels of dissolved oxygen had an effect on acidification kinetics and the ability of L. lactis strains to decrease the redox potential in milk (Larsen et al, 2015). In this study, global gene expression of L. lactis subsp.…”
Section: Introductionmentioning
confidence: 95%
“…The drop in E h value of milk was explained in literature by the consumption of dissolved oxygen and the biological reducing activity of L. lactis (Jeanson et al ), and L. lactis and L. mesonteroides (Larsen et al ). To prove this hypothesis, Jeanson et al () used a mutant that could not consume dissolved oxygen and found that this mutant reduced the culture medium, which confirmed the presence of reducing activity system in L. lactis .…”
Section: Resultsmentioning
confidence: 96%
“…The decrease in E h7 value of the samples would be related to the consumption of dissolved oxygen in the first phase of fermentation followed by the production of metabolites with reducing property by the bacteria (Cachon et al ; Jeanson et al ; Larsen et al ). Living organisms are generally capable of producing antioxidants such as NADH, NADPH, glutathione and uric acid to reduce the damage of oxidative stress (Lin and Yen ).…”
Section: Resultsmentioning
confidence: 99%
“…A relação entre pH, ácido lático e número de micro-organismos foi completamente elucidada durante a década de 1920 e até hoje é explorada pela tecnologia de alimentos (1) . Essa relação ainda serve de base legal para provas que mensuram a acidez do leite brasileiro, como a acidez na escala Dornic, um parâmetro indireto para pH e contagem de micro-organismos (2) .…”
Section: Introductionunclassified